1995
DOI: 10.1007/bf00015533
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater planarian Dugesia sicula Lepori from Sardinia (Platyhelminthes, Tricladida)

Abstract: Fissiparous strains of freshwater triclads of the Dugesia gonocephala group were collected from 12 localities in Sardinia all situated not more than 5 kilometers from the coast. Some environmental factors and the sexual status of the specimens were noted at the time of collection. During the laboratory rearing 30% of individuals of each strain became sexual (ex-fissiparous individuals). All the examined strains showed common karyological and morphological characteristics suggestive of the species Dugesia sicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…In the genus Dugesia chromosome heteromorphism and aneuploidy is a common trait shared by fissiparous populations (Benazzi & Benazzi Lentati, 1976;Ball, 1979;Benazzi Lentati & Deri, 1980;Oki et al, 1981;Lepori & Pala, 1982;De Vries, 1986;Benazzi Lentati et al, 1987a, b;Ribas M., 1990, Ph.D. thesis, Univ. of Barcelona;Tamura et al, 1991Tamura et al, , 1995Tamura et al, , 1998Pala et al, 1995). A plausible explanation of rearrangement and numerical variation phenomena in the chromosome complement could be adaptive selection under the pressures of environmental constraints, as suggested also for the condition of mixoploidy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the genus Dugesia chromosome heteromorphism and aneuploidy is a common trait shared by fissiparous populations (Benazzi & Benazzi Lentati, 1976;Ball, 1979;Benazzi Lentati & Deri, 1980;Oki et al, 1981;Lepori & Pala, 1982;De Vries, 1986;Benazzi Lentati et al, 1987a, b;Ribas M., 1990, Ph.D. thesis, Univ. of Barcelona;Tamura et al, 1991Tamura et al, , 1995Tamura et al, , 1998Pala et al, 1995). A plausible explanation of rearrangement and numerical variation phenomena in the chromosome complement could be adaptive selection under the pressures of environmental constraints, as suggested also for the condition of mixoploidy.…”
Section: Discussionmentioning
confidence: 98%
“…Species belonging to the genus Dugesia, sharing very similar external morphology, but consistently diverging at the level of internal genital anatomy and karyology (Benazzi & Benazzi Lentati, 1976), were usually ascribed to the "D. gonocephala group" until the phylogenetic analysis results of De Vries & Sluys (1990-In spite of very numerous morphological studies focusing on species-specific diagnostic traits, karyological analyses are very scant with the exception of several western Palaearctic and Oriental species (Lepori, 1948;Dahm, 1963Dahm, , 1967Benazzi & Banchetti, 1973;Ball, 1974Ball, , 1977Ball, , 1979Bromley, 1974Bromley, , 1977Benazzi & Benazzi Lentati, 1976;Kawakatsu et al, 1976Kawakatsu et al, , 1989Gourbault, 1981;Oki etal, 1981;Pala et al, 1981Pala et al, , 1995Pala et al, , 1999De Vries, 1986, 1988aRibas etal, 1988;Deri etal, 1999). The genus Dugesia is notably common in a wide geographic range from Europe, Asia including many islands of SE Asian countries, Africa, to NE Australia (70 species are known at present; cf.…”
Section: Introductionmentioning
confidence: 99%
“…This species is mainly composed of fissiparous populations (Pala et al 1995;Charni et al 2004;Lázaro et al 2009) and a few sexual natural populations reported from Mallorca, Algeria and Tunisia (Gourbault 1981;Harrath et al 2012;cf. Stocchino et al 2012).…”
Section: Species With Fissiparous Sexual and Mixed Natural Populatiomentioning
confidence: 99%
“…Faunistic investigations of Sardinian epigean waters, promoted first by Benazzi (1938) and subsequently further developed by Lepori and co-workers, highlighted a considerable taxonomic richness and endemicity of the Tricladida (Lepori, 1951;Pala et al, 1980aPala et al, ,b,c, 1981Pala et al, , 1995Pala et al, , 1999Pala et al, , 2000Casu et al, 1982;Stocchino et al, 2005). In contrast, very few data are available on the Sardinian groundwater triclads, dating back to 1938 when Benazzi recorded Atrioplanaria sp.…”
Section: Introductionmentioning
confidence: 99%